The Association Between Perimenopausal Women's Knowledge and Educational Attainment and Their Readiness for Menopause - Dwi Margareta Andini; Anggraini Dyah Setiyarini (Health and Technology Journal (HTechJ), 2025)
Women go through a phase called menopause, during which their menstrual periods stop during the climacteric era. Around age 45, ovarian function starts to deteriorate, which lowers the production of the hormone estrogen. Given that many women experience anxiety or fear during this time, they must know about menopause. This study's goal is to ascertain how perimenopausal women relate their degree of education and knowledge to their preparedness for menopause. This study uses a cross-sectional research design and is quantitatively analytical. Six hundred forty-one perimenopausal women made up the study population. Purposive sampling was used, and there were 89 participants in the sample. Research Results: Based on the results of the knowledge analysis, 48 ​​respondents (53.9%) had good knowledge, 30 respondents (33.7%) had sufficient knowledge, and 11 respondents (12.4%) had insufficient knowledge. The analysis results of respondent readiness were in the category of ready-to-face menopause, with 67 respondents (75.3%) and 22 respondents (22.7%) not ready to face menopause. The chi-square non-parametric analysis test shows that the significance value obtained is 0.000. It can be concluded that there is a relationship between knowledge and readiness to face menopause in perimenopausal. There is a relationship between education level and readiness to face menopause in perimenopausal women with a value of p = 0.000.